TEACHING PRAGMATIC VARIATION: ADAPTING LANGUAGE INSTRUCTION TO DIVERSE CONTEXTS (Emergent: Journal of Educational Discoveries and Lifelong Learning (EJEDL), 2023)
This scientific article explores the significance of teaching pragmatic variation in language instruction, emphasizing the need to adapt teaching methods to diverse contexts. Pragmatic variation, the nuanced use of language in different social and cultural contexts, is a fundamental aspect of effective communication. This article discusses the challenges of teaching pragmatic variation and provides insights into tailored instructional strategies that can enhance language learning experiences. Drawing upon recent research and educational theories, this study offers practical recommendations for educators aiming to foster linguistic competence and cultural understanding among learners.